Winthrop Sargent papers - Sargent, Winthrop, 1753-1820.
Correspondence, reports, and other papers chiefly relating to Sargent's appointment as governor of the Mississippi Territory (1798-1801) and Federalist Party politics. Correspondents include Manuel Gayoso de Lemos, Timothy Pickering, and James Wilkinson.
Governor of the Mississippi Territory and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gayoso de Lemos, Manuel, -- 1747-1799 -- Correspondence; Pickering, Timothy, -- 1745-1829 -- Correspondence; Wilkinson, James, -- 1757-1825 -- Correspondence; Federal Party (U.S.); Alabama -- History -- To 1819.; Mississippi -- History -- To 1803.; United States -- Politics and government -- 1797-1801.; Army officers; Governors -- Mississippi